Pengaruh Jumlah Penduduk dan Upah Minimum Regional terhadap Kesempatan Kerja di Kalimantan Tengah: The Influence of Population and Regional Minimum Wage on Employment Opportunities in Central Kalimantan - Harati, Rima (Anterior Jurnal, 2024)
This study aims to analyze the Effect of Population and Regional Minimum Wages on Employment Opportunities in Central Kalimantan and this study was conducted in Central Kalimantan with a time span of 2014-2023 using multiple regression analysis tools and classical assumption tests. The results of the analysis concluded that the population (X1) simultaneously did not have a significant effect on increasing employment opportunities in Central Kalimantan. Regional minimum wages (X2) simultaneously had a significant effect on increasing employment opportunities in Central Kalimantan. Based on classical assumptions, it is explained that this regression model meets the assumption of normality, multicollinearity occurs in this regression model, there are no symptoms of heteroscedasticity in the regression model used, it is concluded that in the regression model there are no symptoms or problems of autocorrelation.